SPE Middle East Oil &Amp; Gas Show and Conference 2017
DOI: 10.2118/183942-ms
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Approach to Develop a Colloidal Silica Based Gel System for Water Shut-Off

Abstract: Undesirable water production can significantly affect the economic life of producing wells. Excess water production results in loss of productivity, corrosion, and scaling. Also, the need for water handling facilities and reinjection of unwanted water can further add to the total cost of the project, which consequently increases the cost of production. In offshore operations, produced water can have an adverse impact on the environment. The use of a colloidal silica based fluid system was develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…The strongest difference is observed between NaCl and Na 2 SO 4 which is in tandem with data reported by Huang et al (67). Hamer and Wu (88) and Goldberg (89).…”
Section: Co-ion Effectssupporting
confidence: 88%
See 1 more Smart Citation
“…The strongest difference is observed between NaCl and Na 2 SO 4 which is in tandem with data reported by Huang et al (67). Hamer and Wu (88) and Goldberg (89).…”
Section: Co-ion Effectssupporting
confidence: 88%
“…There are two regimes by which silica particle aggregation can proceed. These are known as reaction limited cluster aggregation (RLCA) and diffusion limited cluster aggregation (DLCA) (65)(66)(67). In RLCA not all collisions lead to the formation of an aggregate.…”
Section: Aggregation Of Silica Sols -Gelling Mechanicsmentioning
confidence: 99%
“… 76 , 92 100 Nevertheless, few studies reported the application of NPs for shutoff purposes. 12 , 59 , 60 , 101 105 When a magnetic field was applied, magnetorheological smart fluids demonstrated reversible and swift liquid-to-solid-like transfiguration. 106 , 107 Accordingly, magnetic NP-based well fluids are ideal for water shutoff and conformance control, especially since external magnetic field applications to oil reservoirs have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Silica gel formation from silica nanoparticles is widely employed in water shutoff services in oil wells [1,2] and was recently proposed to be used in geothermal applications [3].…”
Section: Introductionmentioning
confidence: 99%